2015
DOI: 10.3233/rnn-140448
|View full text |Cite
|
Sign up to set email alerts
|

Can transcranial direct current stimulation be useful in differentiating unresponsive wakefulness syndrome from minimally conscious state patients?

Abstract: Purpose: Disorders of consciousness (DOC) diagnosis relies on the presence or absence of purposeful motor responsiveness, which characterizes the minimally conscious state (MCS) and the unresponsive wakefulness syndrome (UWS), respectively. Functional neuroimaging studies have raised the question of possible residual conscious awareness also in clinically-defined UWS patients. The aim of our study was to identify electrophysiological parameters, by means of a transcranial magnetic stimulation approach, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 115 publications
0
36
0
Order By: Relevance
“…A long duration tDCS protocol applied to MCS and VS patients showed that all patients with MCS had clinical improvement immediately after tDCS, but no patient in VS showed immediate improvement (Angelakis et al 2014). Another study demonstrated that tDCS can boost cortical connectivity and excitability in MCS and VS patients (Naro et al 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…A long duration tDCS protocol applied to MCS and VS patients showed that all patients with MCS had clinical improvement immediately after tDCS, but no patient in VS showed immediate improvement (Angelakis et al 2014). Another study demonstrated that tDCS can boost cortical connectivity and excitability in MCS and VS patients (Naro et al 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…One could concern that the relatively small sample size limits the significance of multiple comparisons made (as the required sample size increases linearly with the logarithm of the number of comparisons made). However, the required sample size for detecting a between-group difference between TDCS after-effects using the typical conventions of 80% power, a two-tailed alpha of 0.05, and a putative metaplasticity effect size of approximately 0.40 (in keeping with the available literature data on TDCS in patients with DoC), [98][99][100][101][102][103][104][105] should be of at least 35 subjects, 106,107 which is satisfied by our sample. Further, the differences between the patients with DoC were statistically significant, as also shown by the effect size data indicating a big effect of TDCS on SICI, above all.…”
Section: Limitation and Conclusionmentioning
confidence: 55%
“…Given the small number of available studies dealing with TDCS in patients with DoC, [100][101][102][103][104][105] we can only try to quantify the relevance of our method in comparison with the other state-of-the-art methods. Our data indicate that metaplasticity is valuable in differentiating patients with DoC.…”
Section: Limitation and Conclusionmentioning
confidence: 99%
“…The rationale of using NIBS to highlight neural patterns potentially subtending awareness relies on the fact that awareness recovery requires that neuroplasticity mechanisms reach a determined threshold for awareness to emerge [131]. This issue was well evidenced by several experimental approaches, including the assessment of EEG oscillatory microstate occurrence (fast alpha and theta/delta), and brain operational architectonics (size, instability, speed of growth, and life span of neuronal assemblies; number and strength of connections; and strength of the DMN synchrony) [132][133][134][135][136][137][138][139][140][141]. Indeed, NIBS can furnish the required, still missing amount of neuroplasticity allowing awareness to emerge, even transiently [37,[76][77][78].…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%